2015
DOI: 10.1136/annrheumdis-2015-208360
|View full text |Cite
|
Sign up to set email alerts
|

Signal intensity alteration in the infrapatellar fat pad at baseline for the prediction of knee symptoms and structure in older adults: a cohort study

Abstract: IPFP signal intensity alteration at baseline was associated with knee structural abnormalities and clinical symptoms cross-sectionally and longitudinally in older adults, suggesting that it may serve as an important imaging biomarker in knee OA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
91
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 81 publications
(99 citation statements)
references
References 45 publications
5
91
3
Order By: Relevance
“…As stated before, the infrapatellar or Hoffa's fat pad is currently a topic of avid research with a number of recent publications [3,8,53]. In contrast, the SPFP fat pad has been less well studied, which is why this longitudinal analysis adds important insights into the role of fat pads in knee joint degeneration.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As stated before, the infrapatellar or Hoffa's fat pad is currently a topic of avid research with a number of recent publications [3,8,53]. In contrast, the SPFP fat pad has been less well studied, which is why this longitudinal analysis adds important insights into the role of fat pads in knee joint degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that an increase in signal intensity on fluid-sensitive fat-saturated sequences, representing an increase in tissue fluid referred to as edema, is sensitive in the acute phase of the disease [4,5,45]. More recently, it has been suggested that the infrapatellar fat pad also plays a relevant role in the development of OA [1][2][3]. OA is a disease with multifactorial pathophysiology, including inflammatory processes, modulated by mediators, some of which ultimately accelerate cartilage degeneration [46][47][48][49][50][51][52].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The biomarkers of osteoarthritis are I type urinary pyridine (pyridine PYD), the C and N end peptide collagen cross linking peptide (CTX-I) is an indicator of the degree of the osteoarthritis, but detection of PYD and the end need ELISA kit and microplate reader, which price is higher and is not suitable for economic conditions a little worse [10,11]. As a marker of osteoarthritis, serum calcitonin (calcitonin) does not apply to all groups of people, and it is not applicable to some patients.…”
Section: Introductionmentioning
confidence: 99%